Q: Simplify the expression (4x and minus 3)(x plus 5).?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x + 8

-5y2+3x+2y

Factorise it: (x + 5)(3x - 8)

5x + 4

Collect like terms: 3x - x + 4x - 4y + 6y + 2 = 6x + 2y + 2

Related questions

3x + 8

-5y2+3x+2y

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

Combine like terms. 6x - 2y +7.

Factorise it: (x + 5)(3x - 8)

5x + 4

7(3y-2)-(-4y+9)

That can be factored to (3x - 5)(3x - 5) or (3x - 5)2

Collect like terms: 3x - x + 4x - 4y + 6y + 2 = 6x + 2y + 2

This quadratic expression cannot be factored because its discriminant is less than zero

You can't simplify this expression. You can calculate a value (a number) only if you happen to know how much "x" is.

I assume you wish to simplify the expression (x - 2)/(3x + 9) . (2x + 6)/(2x - 4) = (x - 2)(2x + 6) / [(3x + 9)(2x - 4)] = 2(x - 2)(x + 3) / [6(x + 3)(x - 2)] = 1/3.